Efeitos da terapia motora cognitiva no desempenho de atividades de crianças com transtorno do desenvolvimento da coordenação - Clarice Ribeiro Soares Araujo (2010)
Children who have difficulty doing daily tasks that require motor skills, such as dressing, playing ball games or riding a bike, that reflect negatively on their participation at home, school and in community, are often called "clumsy" and many technical terms are used to refer to this problem. Currently, the term most widely used is Developmental Coordination Disorder (DCD). Many children do not overcome these problems and when they reach adolescence and adulthood, in addition to motor problems, they present other issues such as social isolation, depression and anxiety. Since DCD has impact across life span it is important to create resources to manage the problem. There are several alternatives for treating DCD, thus, in the present study we used a motor cognitive approach called Cognitive Orientation to Daily Occupational Performance or CO-OP. The objectives of this study were: to explore the use of the CO-OP protocol in the treatment of Brazilian children with DCD; to investigate the effects of CO-OP in the performance of activities; to examine whether, after doing CO-OP, children were able to transfer and generalize the use of strategies and skills acquired to improve functional performance in other activities and contexts. Single case designs with eight children with DCD, ages between six and ten years old, assessed with the Developmental Coordination Disorder Questionnaire (DCDQ-Brazil), the Child Behavior Checklist (CBCL), the Swanson, Nolan and Pelham Scale IV (SNAP IV), answered by their parents, the Movement Assessment Battery for Children-2 (MABC-2), the Wechsler Intelligence Scale for Children-III (WISC-III) administered by external evaluators, the Perceived Efficacy and Goal Setting System (PEGS), the Canadian Occupational Performance Measure (COPM) and Performance Quality Rating Scale (PQRS), to identify goals and to measure changes in occupational performance. After the assessment, the children participated in 13 treatment sessions based on a CO-OP adapted protocol. The data analyzed showed that even though a number of children did not show progress in motor performance, as measured by MABC-2, the occupational performance of all the children improved significantly, seven children were able to generalize learning and six children used the strategies and skills acquired in therapy to learn other tasks. The results showed that the CO-OP program is a viable treatment option for children with DCD in Brazil, and should be further investigated in other formats and with larger samples.